Societcietmeaia and its Representations in Contemporary Theatrical Discourse - Mahmood Mashi, Rafid (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The theater works since its inception, dealing with the problems of society, and simulates the assumptions and requirements, as well as the fact that the theater is one of the most important means of entertainment, and learning at the same time. This has led to increased interest in the intellectual aspects that are being addressed, especially the subject of the social aspect, which is one of the topics that took a wide range in theater treatments, especially after the prevalence of modern philosophies (controversy, doubt, existentialism) after the Age of Enlightenment, and the tendency towards material evidence, and move away from the world of ideals, and metaphysics.